2007
DOI: 10.1111/j.1748-1716.2007.01705.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes‐induced hyperfiltration in adenosine A1‐receptor deficient mice lacking the tubuloglomerular feedback mechanism

Abstract: This study shows that the A1AR(-/-) mice develop diabetes-induced glomerular hyperfiltration, demonstrating that the TGF mechanism is not the major cause of the development of hyperfiltration. Furthermore, the hyperfiltration in the present study was not related to alterations in the glomerular filtration area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…In such a case, some degree of hyperfiltration would persist in the absence of A 1 Rs while the macula densa salt would convert from subnormal to supranormal. While distal salt delivery has not been measured in A 1 R–/– diabetic mice and A 1 R–/– diabetic mice did not hyperfilter in our hands, two other studies have reported hyperfiltration in A 1 R–/– diabetic mice [29, 30]. However, in one study the nondiabetic A 1 R–/– but not the alloxan-diabetic A 1 R–/– mice were hypotensive compared with their WT controls during measurements of GFR [29].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In such a case, some degree of hyperfiltration would persist in the absence of A 1 Rs while the macula densa salt would convert from subnormal to supranormal. While distal salt delivery has not been measured in A 1 R–/– diabetic mice and A 1 R–/– diabetic mice did not hyperfilter in our hands, two other studies have reported hyperfiltration in A 1 R–/– diabetic mice [29, 30]. However, in one study the nondiabetic A 1 R–/– but not the alloxan-diabetic A 1 R–/– mice were hypotensive compared with their WT controls during measurements of GFR [29].…”
Section: Discussionmentioning
confidence: 59%
“…While distal salt delivery has not been measured in A 1 R–/– diabetic mice and A 1 R–/– diabetic mice did not hyperfilter in our hands, two other studies have reported hyperfiltration in A 1 R–/– diabetic mice [29, 30]. However, in one study the nondiabetic A 1 R–/– but not the alloxan-diabetic A 1 R–/– mice were hypotensive compared with their WT controls during measurements of GFR [29]. This is in contrast to two previous reports on the same mouse strain, which concluded that blood pressure under isoflurane anesthesia as well as in conscious mice is higher in A 1 R–/– compared with WT control mice [21, 31].…”
Section: Discussionmentioning
confidence: 59%
“…However, diabetes-induced glomerular hyperfiltration has been shown to occur in mice deficient in the adenosine receptor A 1 , which lack the tubuloglomerular feedback mechanism. 44 Further studies are therefore needed to determine whether the mechanisms proposed in the etiology of glomerular hyperfiltration in animal models can be applied to human patients with diabetes. 28 Interestingly, increased proximal tubular sodium reabsorption has also been demonstrated in obese individuals without diabetes but was thought to be a consequence rather than a cause of glomerular hyperfiltration because the increased filtration fraction increases postglomerular oncotic pressure and therefore favors sodium reabsorption.…”
Section: Glomerular Hyperfiltration In Diabetesmentioning
confidence: 98%
“…131 Hyperfiltration was higher in Ins2 +/-Akita diabetic mice that lacked A 1 adenosine receptors than in wild-type mice; 132 however, no differences in glomerular filtration between alloxan-induced diabetic A 1 adenosine receptor knockout and wild-type mice were observed. 133 Infiltration of macrophages (mediated by the release of lysosomal enzymes) and production of nitric oxide, reactive oxygen species, transforming growth factor β (TGF-β), TNF and IL-1, have pivotal roles in the develop ment and progression of diabetic nephropathy. 134 The A 2A adenosine receptor agonist ATL-146e protects against diabetic nephropathy in rats with streptozotocin-induced diabetes mellitus by reducing glomerular inflammation; 135 activation of A 2A adenosine receptors reduced the infiltration of macrophages, with consequent decreases in the urinary levels of several proinflammatory cytokines, such as TNF, monocyte chemoattractant protein 1 and IFN-γ.…”
Section: Diabetic Nephropathymentioning
confidence: 99%